Comment on “An aesthetic investigation of modern landscape design in light of postmodernism: pop doctrine” - Ying Liu (Trans/Form/Ação)
Commented article: SHEN, Q; WANG, W. L. An aesthetic investigation of modern landscape design in light of postmodernism: pop doctrine. Trans/Form/Ação, Marília, SP, v. 47, n. 4, p. e0240049, 2024. Avaliable at: https://revistas.marilia.unesp.br/index.php/transformacao/article/view/14521.